FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND POLICY DENGAN PROFITABILITY SEBAGAI VARIABEL MODERASI - Angelica Angelica; Rini Tri Hastuti (Jurnal Paradigma Akuntansi, 2023)
This study aims to determine the effect of liquidity and total asset turnover on dividend policy with profitability as a moderating variable in manufacturing companies listed in the Indonesian Stock Exchange in 2018-2020. The sample was selected using the purposive sampling method, and the valid data were 39 companies. The data processing technique in this study uses multiple regression analysis assisted by Eviews version 12 and Microsoft Excel 2010. This study indicates that liquidity and total asset turnover have an insignificant negative impact on dividend policy. Profitability doesn't moderate the effect of liquidity on dividend policy. However, profitability can moderate the effect of total asset turnover ondividend policy. The implication of this research is to know the importance of analyzing the company's performance to improve dividend policy and attract investors to invest.